A Qualitative Study of Social Construction in Boboiboy and Its Implications for Elementary Education - Fauziah, Siti Alfi; Baiquni, Achmad; Hamdani, Djaswidi Al; Rizal, Soni Samsu (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2026)
Amidst the rapid currents of the postmodern era, children's media narratives no longer present a singular, black-and-white reality; rather, they are replete with fragmentation of meaning, moral ambiguity, and cultural hybridity. The animated series Boboiboy emerges as a popular culture artifact exercising strong dominance in constructing the imagination of children across the Nusantara region regarding the figure of the